Analysing soccer using perturbation attempts - James, N.; Rees, G. D.; Griffin, E.; Barter, P.; Taylor, J.; Heath, L.; Vuckovic, G. (Journal of Human Sport & Exercise, 2012)
Dynamical systems theory describes how behaviours can deviate through a series of states (stable or unstable) before returning to an original stable state. It has been suggested that squash performance exhibits properties akin to a dynamical system and demonstrated that squash experts were able to reliably discriminate weak or strong shots that gave one player a distinct advantage over their opponent. They argued that experts were essentially identifying "perturbations" which they defined as incidents that change a system state from a stable to an unstable situation or vice versa. Similarly, in this paper we examine ball possession in soccer and consider those where neither team has a distinct advantage as being a stable situation and perturbation attempts as those where an effort is made to gain a distinct advantage. This study assessed the relative frequency and success rate of perturbation attempts in relation to the match status (match score at the time of the incident). A hand notation system was designed to record the variables of interest (players involved, pitch locations, behaviours performed and behaviour outcomes). Eight domestic league matches from the 2007/2008 season involving a Coca-Cola League One team were analysed. Results indicated that the home team made significantly less perturbation attempts (11.78% of total possessions) compared to the away teams (17.54%) but that generally perturbation attempts were more likely to be unsuccessful than successful (Z = 2.37, p < 0.05). Future studies need to assess if the frequency of perturbation attempts and perturbation success rates are related to playing standard.